“We are the same, we are equal”: Plant diversity knowledge in Indonesian elementary special school textbooks - Afrianto, Whisnu Febry; Adidarma, Dwitya Sobat; Tanjungsari, Rahila Junika; Tanjungsari, Rahila Junika; Wati, Susanti Indriya; Metananda, Arya Arismaya; Ilham, Muhammad (Ethnobotany Research and Applications, 2024)
Background: Education for students with disabilities continues to develop to meet the demands of changing times so that students with disabilities can receive learning in an inclusive environment and their talents and interests continue to develop. The research aims to determine plant diversity in Indonesian textbooks based on class, disability specifics, and book themes at the elementary school level. Methods: The data was collected from 190 books from six grades and five disability categories (blind, deaf, autistic, physically disabled, and mentally disabled). Results: The results found 172 plant species from 61 families. The total frequency was 3642 from all textbooks, and the species that had the highest relative frequency levels was Cocos nucifera (8.79%). The book with the highest species frequency was fifth grade autistic, with 387. Based on content analysis in each chapter, it was found that the cultural score in first grade and instrumental in sixth grade was the highest, with 80 chapters. The dominant plant type was herbaceous at 63.95%. Plants were also categorized into several different types. Several types of threatened species were also found in the textbook. Most of the plants discussed were in the horticultural category. Conclusions: The results of this research can be a reference regarding plant content to better explore threatened species as a conservation education effort. Apart from that, the low level of introduction of plants in textbooks could be reviewed for more effective methods for introduction. Keywords: disability, diversity, plant, special school, textbook Abstrak Latar belakang: Pendidikan untuk siswa dengan disabilitas terus berkembang untuk memenuhi tuntutan perubahan zaman agar siswa dengan disabilitas dapat menerima pembelajaran di lingkungan yang inklusif serta bakat dan minatnya terus berkembang. Penelitian ini bertujuan untuk mengetahui keanekaragaman tumbuhan pada buku teks pelajaran di Indonesia berdasarkan kelas, disabilitas, dan tema buku di tingkat sekolah dasar. Metode: Data dikumpulkan dari 190 buku dari enam kelas dan lima kategori disabilitas (tunanetra, tunarungu, autis, tunadaksa, dan tunagrahita). Hasil: Hasil menunjukkan terdapat 172 spesies tumbuhan dari 61 famili. Total frekuensi adalah 3642 dari semua buku teks, dan spesies yang memiliki tingkat frekuensi relatif tertinggi adalah Cocos nucifera (8,79%). Buku dengan frekuensi spesies tertinggi adalah Kelas lima Autis, dengan 387 spesies. Berdasarkan analisis konten pada setiap bab, ditemukan bahwa skor kultural pada kelas satu dan instrumental pada kelas lima adalah yang tertinggi, dengan 80 bab. Jenis tanaman yang dominan adalah herba sebesar 63,95%. Tumbuhan juga dikategorikan ke dalam beberapa jenis yang berbeda. Beberapa jenis spesies yang terancam punah juga ditemukan di dalam buku teks. Sebagian besar tanaman yang dibahas termasuk dalam kategori hortikultura. Kesimpulan: Hasil penelitian ini dapat menjadi referensi mengenai konten tanaman untuk lebih mengeksplorasi spesies yang terancam punah sebagai upaya pendidikan konservasi. Selain itu, rendahnya tingkat pengenalan tumbuhan pada buku teks dapat menjadi bahan kajian untuk mencari metode pengenalan yang lebih efektif. Kata kunci: disabilitas, keanekaragaman, tumbuhan, sekolah luar biasa, buku pelajaran